Meaningful work: differences among blue-, pink-, and white-collar occupations. Issue 5 (12th September 2016) - Lips-Wiersma, Marjolein; Wright, Sarah; Dik, Bryan
Abstract : Purpose: The purpose of this paper is to compare the importance currently placed on meaningful work (MFW), and determine the frequency by which it is experienced in blue-, pink-, and white-collar occupations. Design/methodology/approachs: Using the comprehensive meaningful work scale (Lips-Wiersma and Wright, 2012) with 1, 683 workers across two studies, ANOVAs were conducted to examine differences in dimensions of MFW. Findings: While unity with others and developing the inner self were regarded as equally important for white-, blue-, and pink-collar workers, the authors data suggest that white-collar workers placed more importance on expressing full potential and serving others than blue-collar workers. The frequency of experiencing MFW differed across the three groups with white-collar workers experiencing higher levels of unity with others, expressing full potential, and serving others; however no mean differences were found for developing the inner self. Originality/value: This study is the first to empirically investigate an oft-discussed but previously untested question: does the experience of MFW differ across white-, blue-, and pink-collar jobs?